THU0015 Oestrogen dependent regulation of micro-rna in rheumatoid arthritis. (12th June 2018) - Andersson, K.; Pullerits, R.; Forsblad-d'Elia, H.; Erlandsson, M.; Silfverswärd, S.T.; Bokarewa, M.
Abstract : Background: Oestrogen has ameliorating effects on rheumatoid arthritis (RA). Oestrogen receptor (ER) signalling affects micro-RNA (miR) expression and processing in breast cancer, while its effect on miR profile in RA have never been studied. Objectives: To study the effect of the oestrogen replacement therapy and oestrogen receptor signalling on the miR transcription and bioprocessing in RA patients. Methods: The expression of the key miR processing enzymes Dicer, Drosha and DGCR8 was measured in the leukocytes of the peripheral blood of 145 female RA patients (age 53 years, disease duration 9.8 years) by RT-PCR and analysed with respect to the levels of ERα, used as surrogate marker of active ERα signalling. Total RNA was prepared from the serum samples of 46 postmenopausal female RA patients who received treatment with oestradiol (E2), noretisterone acetate, vitamin D3 and calcium (n=22, mean E2 levels 229.4±143.2 pg/ml) or vitamin D3 and calcium supplementation only (n=24, mean E2 levels 30.8±8.7 pg/ml). Serum was obtained after 12 and 24 months of treatment and was stored at −70 °C until the time of analysis. MicroRNA transcription was performed by 3D-Gene microarray measuring >2560 miRs (TATAA Biocenter, Gothenburg). Results: A higher ERα expression in RA female patients was associated with increased transcription of the major miR processing proteins Dicer (p=0.0057), Drosha (p=0.019) and DGRC8 (p=0.0095). This activated transcription of miR biomachinery could indicate a higher demand and a facilitated miR maturation. The E2-treatment significantly changed the profile, but not the levels, of miRs in serum, where only 50% of the miR transcripts were present both in E2-treated and control samples. Also the profile of miRs related to RA and of those regulating translation of ERα and Dicer, Drosha, and DGCR8 proteins was affected. Extensive bioinformatic analysis of the miR-targeting genes affected during E2-treatment, revealed a reduction of gene clusters aiding autoimmune pathology and the RA-associated molecular processes including DNA replication (p=2.6x10–4), peptidyl-serine phosphorylation (p=2x10–4), protein localization to nucleus and nuclear import (p=5x10–4). Conclusions: Activation of ERα significantly enhances the miR processing, and affects the profile of miR transcription in female RA patients. The change in miR profile during E2-treatment could contribute to a significantly change in the miR landscape and disposition of intracellular processes in RA. Disclosure of Interest: None declared